Prosthetic emergence angle in different implant sites and their correlation with marginal bone loss: A retrospective study - Yuqian Kou; Qing Li; Zhihui Tang (Elsevier, 2023)
Background/purpose: The impact of prosthetic contour on peri-implant health has attracted increasing attention. This study aimed to evaluate the emergence angles in different implant sites and analyze the correlation between emergence angle and marginal bone loss (MBL). Materials and methods: Single-crown implants with at least 5 years of follow-up were investigated in this retrospective study. Emergence angles and MBL were measured via digital radiography. The differences in emergence angles in different implant sites were analyzed using a one-way analysis of variance. Mann-Whitney U test was used to analyze the differences in MBL between groups (emergence angle> 30° and ≤30°), and Spearman's rank analysis was used to analyze the correlation between emergence angle and MBL. Results: A total of 502 single-crown implants were included. For the mean mesial and distal emergence angles of different implant sites, the anterior position were 21.67 ± 10.80 (°) and 22.48 ± 12.78 (°), and the premolar were 26.29 ± 12.78 (°) and 24.30 ± 10.07 (°), and the molar were 34.53 ± 13.27 (°) and 34.48 ± 13.58 (°) respectively. The emergence angles of molar implant sites were significantly greater than those of anterior and premolar (P < 0.001). The Mann-Whitney U test and Spearman's rank analysis revealed that there was no correlation between emergence angle and MBL. Conclusion: There were significant differences in the emergence angles at different implant sites. However, when considering factors such as different sites or types of implants, there was no correlation between emergence angle and MBL, and more comprehensive research should be conducted in the future.